2012
DOI: 10.1016/j.chom.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmodium Calcium-Dependent Protein Kinase Controls Zygote Development and Transmission by Translationally Activating Repressed mRNAs

Abstract: SummaryCalcium-dependent protein kinases (CDPKs) play key regulatory roles in the life cycle of the malaria parasite, but in many cases their precise molecular functions are unknown. Using the rodent malaria parasite Plasmodium berghei, we show that CDPK1, which is known to be essential in the asexual blood stage of the parasite, is expressed in all life stages and is indispensable during the sexual mosquito life-cycle stages. Knockdown of CDPK1 in sexual stages resulted in developmentally arrested parasites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
223
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(236 citation statements)
references
References 35 publications
12
223
1
Order By: Relevance
“…In female macrogametocytes, CDPK1 initiates the release of the translational repression of messenger RNAs (mRNAs) (Sebastian et al ., 2012). Translational repression in macrogametocytes has been linked to components of regulatory ribonucleoprotein complexes.…”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In female macrogametocytes, CDPK1 initiates the release of the translational repression of messenger RNAs (mRNAs) (Sebastian et al ., 2012). Translational repression in macrogametocytes has been linked to components of regulatory ribonucleoprotein complexes.…”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
“…A de novo synthesis study in zygotes identified 91 proteins synthesized only after fertilization, most of which are involved in motility and invasion (Sebastian et al ., 2012). A recent cross‐fertilization study further showed that the zygote/ookinete stage exhibits a maternal phenotype either from maternal mRNA inheritance or transcription of the maternal alleles, while the respective paternal alleles are silenced in these stages (Ukegbu et al ., 2015).…”
Section: The Zygote‐to‐ookinete Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DEAD-box RNA helicase DOZI (Development of Zygote Inhibited) [18] and the LSm protein CITH (CAR-I and Trailer Hitch homolog) [17] are core components of cytoplasmic messenger ribonucleoprotein particles (mRNPs) that function in the storage and stabilization of known repressed mRNAs in the female gametocyte, but are ready for rapid translation during ookinete formation after transmission of the parasite to the mosquito vector [17,18,[38][39][40]43]. Several P. berghei cpw-wpc transcripts were present in the pool of genes affected in cells depleted of DOZI and CITH (Table 4) [17,18].…”
Section: Cpw-wpc Proteins Are Composed Of Arrays Of a Domain Conservementioning
confidence: 99%
“…At the same time, PI-PLC is stimulated, which hydrolyses PIP 2 to generate DAG and IP 3 (Martin et al, 1994;Raabe et al, 2011b), resulting in the release of calcium from internal stores (Billker et al, 2004). Downstream of this signaling cascade, the increased calcium levels are sensed by specific calcium-dependent protein kinases, which in turn control DNA replication and protein biosynthesis (Billker et al, 2004;Ojo et al, 2014Ojo et al, , 2012Sebastian et al, 2012).…”
Section: The Role Of Plasmodial Phospholipases During Life-cycle Progmentioning
confidence: 99%